7 more men : and the secret of their greatness - Metaxas, Eric (Nelson Books, 2013)
"In Seven More Men, the sequel to the acclaimed Seven Men, #1 New York Times bestselling author Eric Metaxas offers more captivating stories of influential heroes. Profoundly inspiring, Metaxas reveals a gallery of historic figures who faced insurmountable challenges with extraordinary resolve"--